CLINICAL ANALYSIS OF ASSOCIATION OF CYSTATIN C AND ATRIAL FIBRILLATION - Ping Liu; Shujian Sui; Dongling Xu (Российский кардиологический журнал)
Some studies have disclosed atrial fibrillation (AF) is associated with inflammation. Cystatin C is not only inflammatory markers but also an independent predictor of cardiovascular events.Aim. We sought to investigate the relationship between serum levels of cystatin C and the occurrence and development of AF.Material and methods. 235 paroxysmal and persistent AF (AF1 group) and 254 permanent AF (AF2 group) patients in AF group and 221 healthy people in control group were prospectively measured for cystatin C, other inflammatory markers, biochemical indicators, left atrial diameter (LAD), left ventricular diameter (LVD) and left ventricular ejection fraction (LVEF).Results. (1) Compared with control and AF1 groups, AF2 group had higher values of cystatin C, high sensitivity C reactive protein (hsCRP), LAD and LVD whereas lower values of LVEF (P<0.05). (2) After adjust for age, gender and body mass index (BMI), correlation analysis showed that serum level of cystatin C was closely related to hsCRP, LAD, systolic blood pressure (SBP) and creatinine, the correlation coefficient were respectively 0,614, 0,520, 0,463 and 0,538 (all P<0,01), but negatively associated with LVEF (r= –0,356, P=0,012) in AF group. (3) Multivariate regression analysis showed the hsCRP, cystatin C, LAD and LVEF entered finally into the regression equation (cystatin C, OR: 3.25, 95%CI: 1.05–10.17, P=0,008).Conclusion. The serum levels of cystatin C has significant correlation with AF, which indicates cystatin C may play an important role in the process of AF development.